Cost‐Utility Analysis of Infliximab with Standard Care versus Standard Care Alone for Induction and Maintenance Treatment of Patients with Ulcerative Colitis in Poland. Issue 5 (2nd May 2016) - Stawowczyk, Ewa; Kawalec, Paweł; Pilc, Andrzej
Abstract : Study Objective: To assess the cost‐effectiveness of infliximab with standard care (e.g., azathioprine, prednisolone, mesalazine, and 6‐mercaptopurine) versus standard care alone for induction and maintenance treatment of patients with ulcerative colitis (UC) in Poland. Design: Cost‐utility decision analytic model. Measurements and Main Results: A Markov model was used to estimate the expected costs and effects of infliximab/standard care and standard care alone. For each treatment option, costs and quality‐adjusted life‐years (QALYs) were calculated to estimate the incremental cost‐utility ratio. The target population consisted of a hypothetical cohort of adult patients with moderately to severely active UC who had an inadequate response to standard treatment, including corticosteroids and 6‐mercaptopurine or azathioprine, or who were intolerant to or had medical contraindications to such therapies. The analysis was performed from the perspective of the Polish public payer over a 30‐year time horizon. The clinical parameters were derived mainly from the Active Ulcerative Colitis Trial (ACT) 1 and ACT 2 and from the Ulcerative Colitis Long‐term Remission and Maintenance with Adalimumab (ULTRA) 2 clinical trial. Different costs and utility values were assigned to the various health states in the model; utility values were derived from a previously published study. Treatment of patients who received infliximab/standard care instead of standard care alone resulted in 0.174 additional QALYs. Treatment with infliximab/standard care was found to be more expensive than treatment with standard care alone from the Polish National Health Fund perspective. The incremental cost‐utility ratio of infliximab/standard care compared with standard care alone was estimated to be 402, 420 Polish zlotys (PLN)/QALY gained (95% confidence interval [CI] 253, 936–531, 450 PLN/QALY gained), which is equivalent to 106, 743 (U.S. dollars)/QALY gained (95% CI 67, 357–140, 968 [U.S. dollars]/QALY gained). Conclusion: Treatment with infliximab/standard care instead of standard care alone resulted in additional QALYs but also additional costs. The incremental cost per QALY gained of infliximab/standard care compared with standard care alone exceeded the willingness‐to‐pay threshold in Poland (equivalent to 33, 400).